1979
DOI: 10.1002/1097-0142(197906)43:6<2414::aid-cncr2820430637>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinoma.A clinical and pathologic study of 125 cases

Abstract: Retrospective clinicopathological study of 125 thyroid carcinoma cases followed for 9 to 19 years was performed. Case selection for unfavorable histologic type and advanced disease was observed for referred cases. All medullary and anaplastic tumors were in patients over age 40; younger patients all had papillary and follicular carcinoma. Actuarial survival rates showed favorable outcome for papillary carcinoma followed by follicular and medullary or anaplastic tumors. Within the papillary carcinoma group, old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 16 publications
1
8
0
2
Order By: Relevance
“…Our observation that patients with papillary carcinoma had a more favourable survival rate than patients with follicular carcinoma is in accordance with some (5,10,11,20,23,25), but not all (8, 19), earlier reports. The stepwise multivariate analysis suggested that follicular histology is a negative prognostic factor even if other variables are taken into account.…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that patients with papillary carcinoma had a more favourable survival rate than patients with follicular carcinoma is in accordance with some (5,10,11,20,23,25), but not all (8, 19), earlier reports. The stepwise multivariate analysis suggested that follicular histology is a negative prognostic factor even if other variables are taken into account.…”
Section: Discussionsupporting
confidence: 93%
“…Fravenhofer et al in his study of 125 cases of thyroid cancer found that 80% of thyroid cancers in individuals under 40 years of age was papillary carcinoma. 14 In present study out of 70 cases 6 cases were of papillary variety and 2 cases were diagnosed as follicular variety accounting to a percentage of 75% and 25% respectively.…”
Section: Resultsmentioning
confidence: 57%
“…There are two major types of intrathyroidal, low grade follicular carcinomas (FCs) and Hurthle cell carcinomas (HCs): widely invasive and minimally invasive (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The latter type forms a solitary lesion in the thyroid and is almost always encapsulated.…”
mentioning
confidence: 99%